Violent Sex Offenders Lack Male Social Support - Gutiérrez-Lobos, Karin; Eher, Reinhard; Grünhut, Christine; Bankier, Bettina (International journal of offender therapy and comparative criminology, 2001)
Social networks and social support generally exert an important impact on the management of crisis and may thus influence prevention and rehabilitation strategies. The authors therefore investigated the social network and support in a group of 62 incarcerated sexual offenders. Irrespective of the underlying diagnosis, offenders were divided into a high-violent group and a low-violent group. A factor analysis resulted in five factors describing specific dimensions of social support. A significantly lower perceived social support was found in the high-violent group as compared with the low-violent offenders concerning the factors "talking about problems and feelings to someone" and "rely on someone." This low support exclusively referred to men outside the family. Neither the number of previous convictions nor length of prior imprisonment predicted the amount of displayed violence. The authors' results are compared with those in the pertinent literature and are discussed in light of relevant therapeutic strategies in prevention and rehabilitation